Evaluating an inpatient deprescribing initiative at a rural community hospital in Ontario. (July 2020) - Gazarin, Mohamed; Devin, Brian; Tse, Darren; Mulligan, Emily; Naciuk, Mary; Duncan, Simon; Burnett, Sean; Hall, Lynn; Elbeddini, Ali
Background: Deprescribing is an effective means to reduce polypharmacy in elderly patients. However, geriatric day care deprescribing services are challenging to implement in rural regions. In this study, we examined whether a subacute care unit of a rural hospital could deliver a comprehensive and multidisciplinary intervention to promote deprescribing in patients and whether this intervention would succeed in achieving significant and lasting deprescribing results. Methods: We conducted a cross-sectional analysis of a deprescribing program at a rural hospital in Eastern Ontario, Canada. Participants were 11 patients, aged 65 or older, who were admitted to the hospital's medical/surgical unit or who presented to the emergency department. Clinicians followed a structured, comprehensive and multidisciplinary approach designed to facilitate deprescribing, which concluded with an outcome evaluation at discharge and follow-up phone calls. Outcomes included the frequency and total number of medications successfully removed, reduced, substituted and restarted after discharge and emergency department visits and hospitalizations 6 months before and after the intervention. Results: Of a total 57 deprescribed medications, 38 were eliminated, 8 were switched to a safer alternative, and 11 were dose reduced. Postdischarge deprescribing reversal occurred in only 5 of 57 deprescribed medications. Among the study population, a 59.2% reduction was observed in the combined number of emergency department visits and hospitalizations 6 months after deprescribing. Conclusions: This feasibility study was successful in showing the potential added value for offering a rehabilitative, subacute care, inpatient, comprehensive and multidisciplinary approach toward patients with complex deprescribing needs. It also showed proof of concept in reducing polypharmacy-induced adverse health outcomes. Can Pharm J (Ott) 2020:153:xx-xx.